PENGARUH TEKNIK BUDIDAYA YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN KERANG KEPAH (POLYMESODA EROSA) DI KECAMATAN KUPANG TENGAH - H. Haru; Fonny J. L. Risamasu; Priyo Santoso (Jurnal Akuatik, 2018)
Abstract - This research has been conducted to determine the effect of different culture techniques (net pen culture techniques, racking techniques and raft techniques) on the growth and sulvival Atactodea striata (Polymesoda erosa) culture in the intertidal area. This research was conducted from April until June 2017, in Laterite village, Kupang Subdistrict. The experimental design used in this study was Randomized Block Design (RAK). Anova's results show that different culture techniques have a significant effect on the growth and length of Atactodea striata (Polymesoda erosa), where the net pen culture techniques get better length and weight compared to rack and raft techniques. The average length of growth in net pen culture technique (0.63 cm), rack technique (0.53 cm), and raft technique (0.37cm) where Fcount (8.17) > Ftable (5.14) (7,51 grams) and raft technique (6,54 gram) where Fcount (74,56) > Ftable (5, 5,54 gram) 14) at a significant level of 5%. Although different culture techniques have a marked effect on growth, it is not significantly different from the life of the Atactodea striata. Keyword : Atactodea Striata, Aquaculture, Growth, Sulvival